Crushed sublingual versus oral ticagrelor administration strategies in patients with unstable angina - Niezgoda, Piotr; Sikora, Joanna; Barańska, Malwina; Sikora, Adam; Buszko, Katarzyna; Siemińska, Emilia; Marszałł, Michał Piotr; Siller-Matula, Jolanta M.; Jilma, Bernd; Alexopoulos, Dimitrios; Fabiszak, Tomasz; Kubica, Jacek (Thrombosis and Haemostasis, 2017)
Oral administration of crushed ticagrelor tablets turned out to be an efficacious method that improves its pharmacokinetics and pharmacodynamics. This strategy, however, is unlikely to eliminate the drug-drug interaction in patients receiving intravenous morphine, as the impairment of the P2Y12 inhibitor absorption related to decreased propulsive motility of the gastro-intestinal tract is the most likely mechanism of interaction. Thus, we designed a pharmacokinetic and pharmacodynamic study setting the feasibility of platelet inhibition with a loading dose of ticagrelor given as crushed tablets sublingually compared with two other ticagrelor loading dose administration strategies: integral tablet given orally and crushed tablet given orally in patients with unstable angina. Ticagrelor and its metabolite AR-C124900XX plasma concentration was evaluated in nine time points (time frame of 6 hours) using liquid chromatography coupled with mass spectrometry; platelet reactivity was evaluated using multiple electrode aggregometry. The area under the plasma concentration-time curve for ticagrelor and AR-C124900XX was significantly higher in patients treated with crushed tablets given orally compared with crushed tablets given sublingually only within the first hour after loading dose (936.9 ± 898.0 vs 368.0 ± 422.4, p=0.042 and 103.4 ± 120.8 vs 31.3 ± 43.9, p=0.031, respectively). Moreover, we showed significantly stronger platelet inhibition in patients receiving crushed ticagrelor orally vs. sublingually at 30 and 45 min after the loading dose (p=0.024 and p=0.016, respectively). Therefore, the administration strategy of ticagrelor determines the pharmacokinetic and pharmacodynamic profile of both ticagrelor and its active metabolite AR-C124900XX.
Keywords: Ticagrelor; crushed ticagrelor administration; sublingual; platelets; unstable angina